2020
DOI: 10.1038/s41467-020-18537-y
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the varicella-zoster virus A-capsid

Abstract: Varicella-zoster virus (VZV), a member of the Alphaherpesvirinae subfamily, causes severe diseases in humans of all ages. The viral capsids play critical roles in herpesvirus infection, making them potential antiviral targets. Here, we present the 3.7-Å-resolution structure of the VZV A-capsid and define the molecular determinants underpinning the assembly of this complicated viral machinery. Overall, the VZV capsid has a similar architecture to that of other known herpesviruses. The major capsid protein (MCP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Enriched inner tegument CVSC complexes were detected in the portal vertex of KSHV, and unlike the high occupancy of these complexes in HSV-1 [ 10 , 16 , 21 ] and HSV-2 [ 23 , 25 , 69 ] C-capsids, the 11 other vertices in KSHV C-capsids are partially and flexibly occupied with the CVSC, reaching approximately one-third of the full occupancy [ 8 ]. It was also shown that C-capsids of HSV-2 and VZV have higher CVSC occupancy than A- and B-capsids [ 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enriched inner tegument CVSC complexes were detected in the portal vertex of KSHV, and unlike the high occupancy of these complexes in HSV-1 [ 10 , 16 , 21 ] and HSV-2 [ 23 , 25 , 69 ] C-capsids, the 11 other vertices in KSHV C-capsids are partially and flexibly occupied with the CVSC, reaching approximately one-third of the full occupancy [ 8 ]. It was also shown that C-capsids of HSV-2 and VZV have higher CVSC occupancy than A- and B-capsids [ 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cryo-electron microscopy has recently provided high-resolution atomic structures of the portal vertex and the CVSC of KSHV [ 8 , 21 ], as well as of HSV-1 [ 9 , 10 , 17 , 22 ], HSV-2 [ 23 , 24 , 25 ], EBV [ 26 , 27 ], and VZV [ 28 ]. These models have shown that the KSHV portal vertex is enriched with the CVSC tegument complexes, and unlike the high occupancy of CVSC in all vertices of HSV-1 and HSV-2 capsids, CVSC complexes on the other 11 vertices of the KSHV capsids were only partially and flexibly occupied, reaching an average of approximately 30% occupancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capsid structure of herpesviruses was resolved by cryo-electron microscopy, which confirmed that the HCMV three-dimensional capsid structure is similar to the alpha- and gamma-herpesviruses’ capsid structure in overall organization [ 7 , 8 ]. The HCMV genome is twice the size of the VZV genome and >50% larger than the HSV-1 genome [ 9 ].…”
Section: Assembly Of Herpesvirus Capsidsmentioning
confidence: 89%
“…Further, it will be of great interest to employ the CryoEM technique to study the structure of LMP1 signalosome. This technique has been recently applied to the capsids of EBV and other herpesviruses [236][237][238][239].…”
Section: Perspectivesmentioning
confidence: 99%